2015
DOI: 10.2478/johr-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Propagation Of ‘Gisela 5’ Rootstock As Affected By Mineral Composition Of Media And Plant Growth Regulators

Abstract: The purpose of the presented study was to determine the best mineral composition of media and plant growth regulators in the micropropagation of the ‘Gisela 5’ (Prunus cerasus × P. canescens) dwarf sweet cherry rootstock. Nodal explants from young healthy shoots were excised and cultured on Murashige and Skoog medium without growth regulators. In vitro raised shoot tips were transferred to three culture media including Murashige and Skoog (MS), Driver and Kuniyuki (DKW) and Lloyd and McCown (WPM) containing be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…As far the root number is concerned, the highest number was obtained by the combinations 5 μΜ IBA -2.5 μΜ NAA, 20 μΜ IBA -2.5 μΜ NAA, 20 μΜ IBA -5 μΜ NAA, 20 μΜ IBA -10 μΜ NAA and 10 μΜ NAA, indicating that IBA and NAA may act synergistically on root elongation. Increasing IBA concentration did not increase root number, unlike the results reported by Fotopoulos and Sotiropoulos, (2005) and Fallahpour et al (2015) in PR 204/84 and GiSelA® 5 respectively. The highest root length was observed under IBA at 5 μΜ and the lowest under the equimolar addition of both auxins at 5 μM.…”
Section: Effect Of Auxin Treatments On Rootingcontrasting
confidence: 68%
“…As far the root number is concerned, the highest number was obtained by the combinations 5 μΜ IBA -2.5 μΜ NAA, 20 μΜ IBA -2.5 μΜ NAA, 20 μΜ IBA -5 μΜ NAA, 20 μΜ IBA -10 μΜ NAA and 10 μΜ NAA, indicating that IBA and NAA may act synergistically on root elongation. Increasing IBA concentration did not increase root number, unlike the results reported by Fotopoulos and Sotiropoulos, (2005) and Fallahpour et al (2015) in PR 204/84 and GiSelA® 5 respectively. The highest root length was observed under IBA at 5 μΜ and the lowest under the equimolar addition of both auxins at 5 μM.…”
Section: Effect Of Auxin Treatments On Rootingcontrasting
confidence: 68%
“…According to the average of years, root length was determined to be between 11.00 mm and 41.69 mm. In in vitro replication studies of the Prunus species, the root length reported as (Sülüşoğlu and Çavuşoğlu, 2013) 1.68-3.29 cm; (Hosseinpour et al, 2015) 1-2.03 cm and (Fallahpour et al, 2015) 1.5-3.1 cm. The results we obtained from the trial are in agreement with the results of the studies on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most harmful diseases of plum sharka (smallpox) (PPV) -Plum pox potyvirus is and now has become a limiting factor in the cultivation of plum fruits due to their premature abscission or deterioration in quality, leading to yield losses of up to 85-100% [5,6] Due to the fact that the domestic plum is a hexaploid, cultigenic species, it is necessary to take this feature into account when working with it in an in vitro culture, selecting for each stage of subcultivation, an individual set of components of the nutrient medium. Over the past decade, in the literature, there are data concerning the experiments on the culture of isolated tissues of certain varieties of plum [4,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The rooting stage is crucial and precedes the adaptation process. Higher efficiency of rhizogenesis of plum varieties on a nutrient artificial medium -MS -Murashige and Skoog (1962), as indicated by the authors working in this direction, there is a need to adjust it taking into account varietal characteristics [5,[7][8][9]. For example, a two-fold diluted MS nutrient medium is proposed [12,13].…”
Section: Introductionmentioning
confidence: 99%